Biologi dan Perilaku Kawin Sycanus annulicornis Dohrn. (Hemiptera: Reduvidae) yang diberi Pakan Larva Tenebrio molitor L. (Coleoptera: Tenebrionidae) - Abdul Sahid; Wahyu Daradjat Natawigena; Hersanti Hersanti; Sudarjat Sudarjat; Entun Santosa (Universitas Sebelas Maret, 2016)
Sycanus annulicornis Dohrn. is an important predatory insect in controlling plant pests especially in soybean and rice plants. These predatory insects have a wide range of prey, especially of the order Lepidoptera. This study aimed to evaluate the growth and development of S. annulicoris fed on Tenebrio molitor L. larvae, as well as to study the mating behaviour. Growth and development of S. annulicornis reared in the laboratory were evaluated by observing the egg incubation period, fecundity, fertility, development stage and number of nymphs, nymphal mortality, sex ratio, longevity of adult insects, and the life cycles. The results showed that the egg incubation period of S. annulicornis was 15–19 days. Females laid eggs 6–9 days as much as 1–4 days after copulation egg groups containing an average of 81 ± 40 eggs for each group of eggs. The average time of the development of 1st, 2nd, 3rd, 4th, and 5th instar, respectively, were 16.6 ± 1.5; 15.1 ± 2.5; 12.0 ± 2.9; 12.4 ± 2.3; and 19.8 ± 2.1 days, with the sex ratio of male : female was 3 : 4. The nymphal mortality only was observed on 1st and 2nd instar with the precentage, respectively, were 35.2 ± 6.5% and 1.2 ± 1.6%. The mean longevity for female and male adults was 48 ± 6 and 39 ± 5 days, respectively. The life cycle of S. annulicornis for male and female were 141 ± 7 and 127 ± 8 days, respectively. Mating behaviours observed on these species comprised arousal and approach (5.2 ± 3.4 min), riding over (5.8 ± 2.7 sec), copulation (14.8 ± 3.2 min), and post-copulation (149.6 ± 188.3 min). Post-copulatory cannibalism was not observed in this species.